Postcolonial Reflections on Research in an Inuit Community - Heather Moquin (Adult Education Research Conference, 2007)
This paper considers the role of non-indigenous researchers within indigenous contexts. I propose the notions of ‘hybridity’ and a ‘third space’ as useful conceptual lenses to understand the intersection of marginalized and dominant knowledge.